Specific Learning Disorders and Eating Disorders: an Italian retrospective study - Salvatore Ferdinando Aruta; Jacopo Pruccoli; Nicole Bandini; Paola Rucci; Antonia Parmeggiani (BMC, 2022)
Abstract Background Although Anorexia Nervosa (AN) patients show dysfunctional behaviour in information processing, visual and verbal memory performance, and different cognitive fields, regardless of their BMI, the literature on the correlations between Eating Disorders (ED) and Neurodevelopmental Disorders (NDD) does not provide conclusive data. Rather than a consequence of the mental disorder, cognitive dysfunctions may be a risk factor for AN. Methods Our retrospective study investigates the prevalence of Specific Learning Disorder (SLD) among patients with ED. We considered 262 patients being treated at the Emilia Romagna Feeding and Eating Disorders Outpatient Service in Bologna, Italy. We compared the results with the Italian reference values, according to the most recent data provided by the Italian Ministry of Education. Results We found that 25 patients out of 262 (9.54%) presented a comorbid diagnosis of SLD. This SLD prevalence is higher than the Italian reference values (4.9% in the school year 2018/19, p < 0.001). Comorbidity with SLD was significantly more frequent in males. A diagnosis of SLD was not associated with a higher frequency of any specific ED diagnosis or with psychiatric comorbidity in general. Positive family history for SLD was not significantly associated with either a positive family history for ED or a diagnosis of SLD. Conclusions This is the first Italian study to investigate the prevalence of SLD in ED patients during childhood and adolescence. Our data support previous research documenting that neuropsychological deficit could lead to the development of ED.